2011
DOI: 10.1017/s1368980011002199
|View full text |Cite
|
Sign up to set email alerts
|

Western and Mediterranean dietary patterns among Balearic Islands’ adolescents: socio-economic and lifestyle determinants

Abstract: Objective: To assess prevailing food patterns among Balearic Islands' adolescents, and socio-economic and lifestyle determinants. Design: Cross-sectional nutritional survey carried out

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
50
0
21

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 62 publications
14
50
0
21
Order By: Relevance
“…Results of this study showed a positive association with statistical significance between the mother’s educational level and the KIDMED index, showing that a higher KIDMED index was linked to higher educational levels. Similar findings in previous studies conducted in countries such as Spain [11, 30] and Turkey [6] also showed that a predictor of adherence to the MD was the mother’s education. Regarding the socioeconomic aspect, our results support the findings of previous Spanish studies [11, 22, 30] since the proportion of participants with medium-to-high incomes that reported an optimal MD was greater than the proportion amongst individuals with low incomes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results of this study showed a positive association with statistical significance between the mother’s educational level and the KIDMED index, showing that a higher KIDMED index was linked to higher educational levels. Similar findings in previous studies conducted in countries such as Spain [11, 30] and Turkey [6] also showed that a predictor of adherence to the MD was the mother’s education. Regarding the socioeconomic aspect, our results support the findings of previous Spanish studies [11, 22, 30] since the proportion of participants with medium-to-high incomes that reported an optimal MD was greater than the proportion amongst individuals with low incomes.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings in previous studies conducted in countries such as Spain [11, 30] and Turkey [6] also showed that a predictor of adherence to the MD was the mother’s education. Regarding the socioeconomic aspect, our results support the findings of previous Spanish studies [11, 22, 30] since the proportion of participants with medium-to-high incomes that reported an optimal MD was greater than the proportion amongst individuals with low incomes. Also, in Italy, particularly in the southern region, one of the major predictors of high adherence to Mediterranean dietary pattern was high socioeconomic status [36].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, good adherence to the MedDiet was positively associated with better academic performance in youths [8]. Despite the health benefits of the MedDiet, several studies have reported that dietary patterns in the Mediterranean region are changing to a more Westernised diet [11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Another study among Spanish children and adolescents showed that more than 2 hours of TV-watching is likely to be associated with the dietary pattern of a high consumption of sweets, salted snacks, bakery products, and soft drinks [9]. On the contrary, a healthy dietary pattern such as the Mediterranean dietary pattern was found to be inversely associated with screen time among European children [10]. However, there is limited information on the association between dietary patterns and screen time in Asian populations.…”
Section: Introductionmentioning
confidence: 99%